Anti-SARS-CoV-2 Antibody Development over Four Years in Blood Donors - Niederhauser, Christoph; Widmer, Nadja; Tinguely, Caroline; Suter Riniker, Franziska; Fontana, Stefano; Buser, Andreas; Waldvogel, Sophie; Thierbach, Jutta; Züger, Max; Gowland, Peter (Viruses, 2025)
The blood donor population has great potential to serve as a sentinel system for the general population. The data presented in this study of a survey of the seroprevalence of Anti-SARS-CoV-2 antibodies in Switzerland are an illustrative example of this possibility. From March 2020 to January 2021, the increase in antibody seroprevalence for both Anti-NCP and Anti-S was only very moderate, up to ~17%. In May/June 2021, the Anti-NCP seroprevalence was 21.6% and the S-seroprevalence 59.4%, respectively, indicating only a moderate natural infection rate. The Anti-seroprevalence rate was in good agreement with the first vaccination campaign launched in winter 2020/21. The dramatic increase in the antibodies against the NCP protein (74.6%) since November/December 2021 to June–August 2022 was simultaneous with the appearance and rapid spread of the Omicron SARS-CoV-2 variant in Switzerland and the abolition of compulsory mask wearing in public spaces. At the end of 2022, 99.0% of the blood donor population already developed antibodies against the S protein and 83.9% against the NCP. One year later, after the official termination of the pandemic, these seroprevalences were even higher, 99.8% for the Anti-S and 95.0% for Anti-NCP. This increase for both of them was in accordance with the vaccination campaigns, the abolition of mask wearing, and the spread of the Omicron variant. These data show how the blood donor population can be used to represent the infection surveillance of the general population of a region or country.